High mach number drag analysis of a modern lightweight launch vehicle. Issue 1 (January 2021) - French, Ainslie D; Schettino, Antonio; Romano, Luca
Abstract: This paper presents predictions of pressure and frictional drag using on the individual components of the VEGA C Light Launch Vehicle propelled by a solid rocket motor over a hypersonic Mach number range from five to eight at nominal atmospheric conditions associated with the corresponding stage of the ascent trajectory. Both motor-off and motor-on conditions are simulated to isolate the motor-on effects. A series of simulations were also performed in off-nominal conditions by varying the Reynolds number and mass flow rate to examine the effects on drag under more extreme conditions. The results indicate that the differences between the motor-off and motor-on cases in nominal conditions are mainly due to base drag. With the motor-on the base pressure increases thereby reducing the total drag. In the off-nominal conditions, when the Reynolds number is increased there is a reduction in drag, and when the nozzle mass flow rate is decreased there is an increase in drag. Conversely, when the Reynolds number is decreased and the nozzle mass flow rate is increased, the opposite effect occurs. However, for very low Reynolds numbers, an incipient separation can occur on the first stage, which also influences the drag.